Manajemen Pendidikan Berbasis Produksi - Arman Syahyudi; Imam Agung Wijaya; Heni Noviarita (An Naba, 2021)
In this study, it will be further discussed how the production of education and the function of production in education will be discussed. The formulation of the problem in this research are; 1) how is the production system in education?; 2) what is the function of production in education. This study uses a qualitative descriptive research approach with the type of literature study. Literature research is carried out through books, magazines, journals, the internet and so on. In addition, by conducting observational studies from previous studies. The results found are; 1) that educational inputs are the basic ingredients of the educational process to produce educational outputs. Education output is classified as consumption and investment. Aspects of consumption related to joy, pleasure, social status, security (reduction of crime rates) and skilled labor; that can be obtained and enjoyed by students, families, and society as a whole. Meanwhile, the investment aspect includes educational outcomes related to increasing the productive skills of a person and society to achieve future prosperity. 2) The production function in education is the administrator's production function, the psychological production function, and the economic production function.